Simultaneous Dual-Task Interventions That Improve Cognition in Older Adults: A Scoping Review of Implementation-Relevant Details - Natasha Versi; Kylie Murphy; Caroline Robinson; Mitchell Franklin (Journal of Aging Research)
Cognitive change occurs as a person ages and may result in decreased cognitive functioning in older adults (60 years and older). Simultaneous dual-task (SDT) interventions—activities that require the person to engage physically and cognitively at the same time—are effective in improving cognition in this group. This scoping review analysed published implementation-relevant details about effective SDT interventions, to assist the translation of the available evidence into various practice needs and contexts. A total of 23 databases were searched for relevant studies published between 2009 and 2020 inclusively. Randomised controlled trials (RCTs) that revealed statistically significant improvement in one or more aspects of cognitive function were appraised for methodological quality, using the Joanna Briggs Institute RCT checklist. The 14 RCTs scoring over 50% on the checklist were further analysed. Implementation-relevant data—for example, intervention nature, session length and frequency, equipment and space requirements, target group, and outcomes—were extracted, collated, and synthesised. The effective SDT interventions varied considerably in their nature and outcomes, meaning that suitable SDT interventions exist for a range of contexts. However, the resources required to implement some of the interventions either were not reported and/or may be prohibitive in some real-world practice contexts. Whilst “challenge” and “group interaction” were common features of effective SDT interventions, most studies failed to report on key implementation details required to facilitate translation into practice. It also remains unclear for how long the cognitive benefits are sustained following an effective SDT intervention. In future, more consistent publication of information about how to implement effective SDT interventions, for whom these interventions are engaging/enjoyable, and why would help to translate the available research into improved cognitive outcomes for older adults.